Pemberdayaan UMKM: Melihat Peluang Bisnis UMKM di Era Digital di Desa Ujunge Kecamatan Tanasitolo Kabupaten Wajo - Fadhillah, Prayudhi; Yuniarti, A. (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
One of the Three Dharmas of Higher Education is the implementation of community service, which aims to develop the abilities of the community. MSME development is a community service activity in the form of applying the results of science and technology to solve problems faced by MSMEs (micro, small and medium enterprises). This program is aimed at increasing the independence and performance of MSMEs. Examples include: increasing business opportunities in the era of digitalization, increasing the productivity of MSMEs with appropriate technology, developing online marketing to expand the MSME market, as is the case in Ujunge village, Tanasitolo District, Wajo Regency, with several MSMEs opening businesses but lacking skills so proficiency is needed. . Therefore, there is a need to socialize the empowerment of MSMEs. In this socialization activity, it is hoped that MSMEs can increase their productivity and gain knowledge to market their products online